Timbre as a marker of cultural territories in electroacoustic music (Orfeu, 2026)
Departing from the field of music theory and analysis in dialogue with cultural studies, this article aims to investigate how timbre can function in electroacoustic music as a marker of social, cultural, and identity territories, even if that genre is supposed to strive for abstraction. Drawing on practical experiences and analyses of works by authors such as Fernando Iazzetta, Denis Smalley, Pierre Schaeffer, Pierre Henry, and Coriún Aharonián, the study shows how the use of certain sounds, such as those from the berimbau, the bagpipes, or native flutes, evoke specific cultural practices, functioning as signs of identity and social differentiation. While in some instances, the use of these timbres may reinforce colonial stereotypes and exoticizations, in others it can assume a critical and decolonial character, affirming resistance and cultural belonging. The article concludes that timbre, in electroacoustic music, is a central element not only for its structural dimension but also for its symbolic dimension, as being capable of representing cultures and enabling narratives.
Keywords: Electroacoustic Music; Timbre; Theory and Analysis; Cultural Studies; Decolonialism